Why does exercise terminate at the maximal lactate steady state intensity? - Baron, B.; Noakes, T. D.; Dekerle, J.; Moullan, F.; Robin, S.; Matran, R.; Pelayo, P. (British Journal of Sports Medicine, 2008)
Objective: The purpose of this study was to measure physiological responses during exercise performed until exhaustion at the exercise intensity corresponding to the maximal lactate steady state (MLSS) in order to determine why subjects stopped.